Mengungkap Potensi Riil Pajak Rumah Sewaan Di Kecamatan Jatinangor - Ella, Susy; Fitria, Rizky (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2011)
Jatinangor Subdistrict is one area in Sumedang that has potential for rental housing business. In recent years, the number of rented house in the Jatinangor continues to increases. Therefore, the Government made the rental Sumedang District as one source pendapaten area by taxing the rental of the house. Taxation policy is set out in Local Regulation No. 52 Year 2001. Then because of the overlap among VAT and income tax, the policy was revoked in 2008 and revised to Local Regulation No. 8 Year 2010. The tax rate is set at five percent and subjected to small rented house with rooms above 10. This paper tries to analyse taxation regarding to rental potential using the data in 2008. The potential seen by taking a sample of 105 rented homes spread over four villages in the district Jatinangor. The potential is then calculated by multiplying the tax rate leases with rental income every home sampled. Data processing results of this study show that the District Jatinangor has huge potential in terms of the rental tax of Rp.921.018.638. Unfortunately, this potential cannot be excavated to the maximum by the District Government Sumedang due various barriers.